2022
DOI: 10.1039/d1cp05414g
|View full text |Cite
|
Sign up to set email alerts
|

First-principles calculations of bulk, surface and interfacial phases and properties of silicon graphite composites as anode materials for lithium ion batteries

Abstract: Lithium stabilizes silicon–graphite interfaces, making hollow core–shell structures favorable in the presence of lithium and yolk–shell configurations favorable in its absence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 84 publications
0
12
0
Order By: Relevance
“…On the other hand, Li ions inserted into the Si host subsystem increase its partial volume by breaking Si–Si bonds in favor of softer Si–Li and Li–Li bonds. Moreover, the higher Li concentrations which both surfaces and grain boundaries exhibit results from the lower tension of Li adatoms . In fact, Figures S.5 and S.21 show that the surface tension of Li x 1 Si compounds with respect to their bulk structure decreases proportionally to their Li content, x 1 .…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…On the other hand, Li ions inserted into the Si host subsystem increase its partial volume by breaking Si–Si bonds in favor of softer Si–Li and Li–Li bonds. Moreover, the higher Li concentrations which both surfaces and grain boundaries exhibit results from the lower tension of Li adatoms . In fact, Figures S.5 and S.21 show that the surface tension of Li x 1 Si compounds with respect to their bulk structure decreases proportionally to their Li content, x 1 .…”
Section: Resultsmentioning
confidence: 96%
“…Indeed, they did not observe crack formation throughout the charge/discharge cycles and proposed the following reversible electrochemical reactions .25ex2ex SiX + 4 Li + + 4 e Si + Li 4 X false( normalX = normalC , 0.25em normalO , 0.25em 0.25em ··· false) Si + 4.4 Li + + 4.4 e Li 4.4 Si These equations imply that Li in SiC, as in SiO x anodes, , likely reacts with the more electronegative element, i.e ., C (O in SiO x ) up to a maximum concentration ( e.g ., Li 4 C for SiC and 2Li 2 O for SiO 2 ) before undergoing exothermic mixing with Si up to the Li 4.4 Si phase. Among nongraphitic compounds, only the Li 2 C 2 salt phase (space group Immm ) is known to be thermodynamically stable at STP. ,, By performing DFT calculations, Lin et al showed that Li y C compounds would stabilize themselves up to y = 8 only if a compressive stress about 40 GPa was applied. The capacity of 309 mA h g –1 measured by Zhang and Xu does not match with the electrochemical equations they suggested in eq , which predicts much higher capacities of about 5626 mA h g –1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations